Trichoepithelioma And Multiple Basal Cell Epithelioma - Dey S.K; Gangopadhyay D.N (Wolters Kluwer Medknow Publications, 1996)
A combination of multiple trichoepithelioma and basal cell epithelioma is reported. Although malignant degeneration of trichoepithelioma is debated, clinical and histopathological studies, in our case, hint at that. The case is reported for its rarity.